Penguatan Literasi Keuangan Digital dan Keterampilan Manajemen Keuangan bagi Anak Yatim di Depok - Johan Hendri Prasetyo; Agus Syukur; Gani Wiharso (PT. Riset Press International, 2026)
Financial literacy is a vital life skill that enables individuals to manage their financial resources effectively and make informed, responsible financial decisions. However, many children from vulnerable groups, including orphans, have limited knowledge about basic financial management. This community service activity aimed to improve financial literacy and simple financial management skills among orphaned children at the Orphan Support Organization of RW 05, 06, and 07 in Depok. The program was implemented through interactive educational sessions, discussions, and practical exercises related to managing personal finances. The material introduced fundamental concepts such as distinguishing between needs and wants, the importance of saving, and the responsible use of money in daily life. Ten participants attended the activity. Evaluation was conducted using questionnaires to measure participant responses and satisfaction with the program. The results showed that participants responded positively to the activity and demonstrated better understanding of basic financial concepts. Most participants expressed high satisfaction with the learning materials and delivery methods. The activity indicated that community-based financial literacy education could effectively increase financial awareness among orphaned children. The program was expected to encourage responsible financial behavior and support participants in managing their financial resources more wisely in the future.